2021
DOI: 10.3390/en14113207
|View full text |Cite
|
Sign up to set email alerts
|

Future of Sustainable Management of Energy Companies in Terms of Attitudes and Preferences of the Younger Generation

Abstract: The future of the energy sector depends on the younger generation. The paper presents the results of the study, the aim of which was to determine to what extent younger generation is pro-ecological and pro-social, and whether they will include pro-ecological and pro-social activities in the management of energy companies. It is especially important to implement sustainable management in the energy sector. The study found that only 33.9% of young people are highly pro-ecological and 28.6% highly pro-social. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, this case can be called a functional area, with strong relationships in terms of a joint labour market, the market of public services, infrastructural networks, and transport connections [54,55]. The completed workshops indicated that local managers also look at the emerging metropolis in terms of relationships developed based on the generation and transfer of broadly understood knowledge [56,57]. The GZM has varying potentials that enable its development towards the networking of intelligent cities.…”
Section: Discussionmentioning
confidence: 99%
“…However, this case can be called a functional area, with strong relationships in terms of a joint labour market, the market of public services, infrastructural networks, and transport connections [54,55]. The completed workshops indicated that local managers also look at the emerging metropolis in terms of relationships developed based on the generation and transfer of broadly understood knowledge [56,57]. The GZM has varying potentials that enable its development towards the networking of intelligent cities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they have a positive attitude to electric cars; they try to buy local and seasonal food products and choose those producers who implement CSR strategies [17,107,140]. Although, sometimes, they have difficulties with some areas because they lack appropriate knowledge and experience [141]. This is the case, for example, in terms of reducing food waste habits and waste reduction [17,142].…”
Section: Generation Z Behavioursmentioning
confidence: 99%
“…Solutions that are based on these solid foundations, are properly implemented and make up the overall smart-city concept also contribute to more efficient urban investments and more sustainable city development. This in turn translates into changes for all stakeholders of the city as an organization (Pabian et al 2021;Stefańska and Bilińska-Reformat 2020;Zanella et al 2014).…”
Section: Review Of the Literature On The Smart-city Conceptmentioning
confidence: 99%